2014
DOI: 10.9755/ejfa.v26i10.18804
|View full text |Cite
|
Sign up to set email alerts
|

Molluscicidal activity of the aqueous extracts from Solanum mammosum L., Sapindus saponaria L. and Jatropha curcas L. against Pomacea canaliculata

Abstract: Biomolluscicides development is of great interest in pest management to avoid the effects on the environment caused by synthetic molluscicides. The Species: Solanum mammosum L., Sapindus saponaria L. and Jatropha curcas L. have demonstrated molluscicidal properties against Pomacea canaliculata. This study was carried with mixtures of aqueous extracts of these plants in order to check for a synergistic effect between them. Extracts obtained from each species were evaporated and lyophilized. By using a simplex c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…This species has invaded several European, North American, and Asian countries and damages rice and aquatic organisms (Accorsi et al 2014 ; Horgan et al 2014 ; Karraker and Dudgeon 2014 ). Given the adverse effect of this species, physical, chemical, and biological control techniques have been established; such methods include crop rotation (Wada et al 2004 ), use of molluscicides (Cruz et al 2000 ; Quijano et al 2014 ), and use of predators (Su Sin 2006 ; Ip et al 2014 ; Yusa et al 2006 ). As an abundant aquatic living resource, utilization of egg of golden apple snails has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…This species has invaded several European, North American, and Asian countries and damages rice and aquatic organisms (Accorsi et al 2014 ; Horgan et al 2014 ; Karraker and Dudgeon 2014 ). Given the adverse effect of this species, physical, chemical, and biological control techniques have been established; such methods include crop rotation (Wada et al 2004 ), use of molluscicides (Cruz et al 2000 ; Quijano et al 2014 ), and use of predators (Su Sin 2006 ; Ip et al 2014 ; Yusa et al 2006 ). As an abundant aquatic living resource, utilization of egg of golden apple snails has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The ethyl acetate soluble fraction of Aglaia duperreana was effective against GAS [26]. In rice field conditions, the molluscicidal efficacy of chemically modified quinoa (Chenopodium quinoa) saponins [27], methanol extract of Camellia oleifera seed meal [28], and Sapindus saponaria extract [29] were tested against GAS. The application of tobacco waste in field trials proved its efficacy with 100% mortality of GAS [30].…”
Section: Introductionmentioning
confidence: 99%
“…Sapindus saponaria L. molluscicidal activity is attributed to the presence of saponins (Pinto et al, 1944), substances that interact with sterols present in cell walls of gills mollusks, causing cell rupture (Karabaliev et al, 2003;San Matins et al, 2009) (WHO, 1983b). (Quijano et al, 2014). Discrepancy between laboratory and field assays may arise because the presence of weed, mud and lower content of dissolved oxygen in the water, factors that reduced the molluscicidal activity of both formulations (Adewunmi and Marquis, 1987;San Martín et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Solanum mammosum L. and Sapindus saponaria L. are natural molluscicide and their combined effect against Pomacea canaliculata has been evaluated under laboratory conditions by Quijano et al (2014); those authors demonstrated that there was not a synergism effect in the combination Sapindus saponaria L. and Solanum mammosum L. (50:50, w/w). 1 (ISSG, www.issg.org/database).…”
Section: Introductionmentioning
confidence: 99%